Digital Inclusion and The Challenges of Accessing G2C Public Services for The Elderly: A Case Study In Bojonegoro Regency - Putri Ana Istiqomah; Ana Kumalasari; Sri Kasiami (Mahesa Research Center, 2026)
This article aims to advance the development of increasingly sophisticated household appliances and digital technology, which are currently trending. However, a group that has been left behind in this modern era remains, namely, older people. Its novelty is that it provides a practical contribution to the Bojonegoro district government so that digital public services are not discriminatory towards older people. The purpose of this article is to gain a deeper understanding of the digital inclusion in public services for citizens (G2C) and the access challenges faced by all older adults in Bojonegoro Regency. The conceptual framework used in this article consists of digital inclusion, G2C public services, the digital divide, and elderly inclusion. This research employs a qualitative approach, utilizing a case study method. The data collection techniques described in this article were conducted through interviews and document analysis. Meanwhile, the data analysis technique used software, namely N'vivoNVivo, to process qualitative research data. The study's results show that internal and external factors act as barriers to older people's access to digital public services in Bojonegoro Regency. The internal factor is the lack of motivation among older people to learn new digital technologies, while the external factor is the lack of elderly-friendly digital technology services. The development of digital technology, especially government-provided digital public services, must overcome the digital divide across all communities in Bojonegoro Regency—practical recommendations for equitable government infrastructure and flexible service approaches.